Modeling and optimization of essential oils and extracts for meat quality evaluation during storage, with high-performance liquid chromatography analysis of aflatoxin levels - Sarah Alharthi; Sarah Alharthi; Rokayya Sami; Hilary Uguru; Ruqaiah I. Bedaiwi; Awatif M. Almehmadi; Suzan A. Abushal; Roqayah H. Kadi; Buthaina M. Aljehany; Eman A. Abduljawad; Abeer A. Aljehani; Sarah S. Aggad; et al. (Frontiers in Sustainable Food Systems)
This research was focused on developing a suitable and optimizing model, for dried meat preservation (storability), through the application of natural essential oils and extracts. The dried meat (beef) samples were treated with onion peels extract (OPE), onion peels oil (OPO), plantain peels extract (PPE), and plantain peels oil (PPO), in accordance with concentrations and hybridization levels, provided by Central Composite Design (CCD) model. Two basic independent variables – treatment type and storage time – were evaluated, to establish their impact on six responses: total bacterial viable content (TBC), Staphylococcus aureus, Salmonella spp., total viable fugal content (TFC), aflatoxin B1 and aflatoxin B2. Based on the CCD optimization guidance, the meat samples were treated with 10 different natural additives, and coded T0 to T9, respectively. Nutritional and microbial evaluations of the samples were done by utilizing standard procedures. Specifically, the High-Performance Liquid Chromatography (HPLC) approach was used to explore the B vitamins and aflatoxins concentrations. The results specified that the plantain and onion waste products safeguarded the meat nutritional integrity and public health safety. Additionally, the optimization result depicted that the hybridized PPO and OPO treatment (T9), demonstrated the optimal efficacy in inhibiting microbial growth, and formation of aflatoxins. The maximum TBC and TFC populations of 3,130 and 2,180 cfu/g, were recorded in the control (T1) meat samples, respectively. The study found that the essential oils and extracts, effectively reduced the aflatoxins B1/B2 levels, in preserved beef to safe limits, established by the World Health Organization for meat products suitable for human consumption. This study’s results have highlighted the effectiveness of using oils and extracts derived from discarded onion and plantain peels, in improving meat quality, integrity and inhibiting pathogens survival.